1946
DOI: 10.1021/ie50435a020
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Plasticity of Undried Cotton Fibers

Abstract: X-ray patterns of undried cotton fibers taken from developing bolls showed little or no evidence of crystalline cellulose. The pattern of native cellulose appeared at the time the fibers underwent their initial dehydration. Undried cotton fibers possessed considerable plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1959
1959
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…' Before tests were performed, the cotton fibers (lint) were dissected from the seeds while the locks were immersed in the storage liquid. Care was taken to exert as little tension as possible on the fibers during dissection, since Berkley and Kerr [4] had concluded that stretching the moist fibers caused some crystallization. The dissected lint was thoroughly mixed before samples were withdrawn for tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…' Before tests were performed, the cotton fibers (lint) were dissected from the seeds while the locks were immersed in the storage liquid. Care was taken to exert as little tension as possible on the fibers during dissection, since Berkley and Kerr [4] had concluded that stretching the moist fibers caused some crystallization. The dissected lint was thoroughly mixed before samples were withdrawn for tests.…”
Section: Methodsmentioning
confidence: 99%
“…Berkley and Kerr [4] latter reported that &dquo;x-ray patterns of undried [italics ours] cotton fibers taken from developing bolls showed little or no evidence of crystalline cellulose,. The pattern of native cellulose appeared at the time the tiht>rs underwent their initial clehyclraticm,~.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Knowledge of relative varicellulose as industrial raw material. Although it ations in degree of polymerization, crystallite size, is generally agreed that native cotton exhibits crystallinity, and orientation of crystallites to the variation in the value of crystallinity between cotton varieties, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] a very narrow spread (67-72%) in crystallinity values by itself is insufficient to crystallinity based on a simplified crystallinemic residues by soaking for 6 h each in carbon tetrachloride and methanol and subsequent boilamorphous system is not very meaningful. [26][27][28] The literature on the crystallite size of cellulose is ing for 3 h in 2% sodium hydroxide solution.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on never-dried cotton fibers (fibers removed from fresh closed bolls and maintained in their original &dquo;biological&dquo; state) discussed their structure, plasticity, and crystallinity [2,7,12]. Since 1971, additional reports have described the unique water uptake, reactivity, fine structure, morphology, and mechanical properties of never-dried cot ton, and the irreversible changes in these properties that occur during the initial drying of the fibers [3-6, 8, 10, 11].…”
Section: Introductionmentioning
confidence: 99%